Thermal anomalies on Savich Cone, Kikhpinych Volcano, Kamchatka: IR surveys and land-based observations for 30 years (1982 through 2012) - Kardanova O.F.; Dubrovskaya I.K.; Murav'ev Ya.D. (My University, 2015)
An analysis of data from nadir aerial thermal surveys of 2010 and 2012, as well as from a land-based IR survey of 2010, showed changes in the thermal regime of anomalies on Savich Cone (Kikhpinych Volcano, Kamchatka) compared with the 1982 and 1993 surveys. It was noted that the temperature increased in the upper part of the cone, new warm patches appeared in the near-crater zone of the cone, and white sublimates appeared in the southwestern and southeastern sectors of the crater. The last feature was new.
Keywords: 38.37.25 Вулканология; Кихпиныч; Kikhpinych; Kamchatka